ANALISIS PROMOSI JABATAN DENGAN SISTEM TALENT SCOUTING OLEH BKD PROVINSI JAWA TENGAH - Tutiyani Tutiyani; Titik Djumiarti (Journal of Public Policy and Management Review, 2018)
Human resources management is one of important things that need to be design to create competen resources who deliver the public service work. Promotion is one of part from human resources management. Province of Central Java having an open system of promotion at echelon III and IV and it calls as talent scouting system. The implementation of talent scouting at Central Java Province will be continue, so then the number of talent pool will be increase. In the other hand the number of promotion are less then the number of talent pool. This research is aimed to know the process of promotion using talent scouting system; and also the driving factors and obstacle factors which are influence the implementation of promotion by using talent scouting system. This research use descriptive method with kualitative approach. The result of this research show that the process of talent scouting divided into four steps which are planning, organizing, actuating dan controlling. Those four steps show there haven’t all of talent pool have their promotion. The driving and obstacle factors consist of organisation employment domands, SIMPEG, culture, structure, the change of employment, technology, economic growth, and government regulation.